Media Puzzle dalam Meningkatkan Hasil Belajar IPAS pada Materi Benua bagi Peserta Didik Kelas VI di SD Negeri 1 Terusan - Fitriyatun Nisa; Wulan Nur Cahyani; Vina Siti Alifah; Arief Hidayat Afendi; Kurinih Kurinih (Mathematics Education Study Program, 2025)
This study is based on the issue that class VI students at SD Negeri 1 Kanan have a hard time grasping continental scientific concepts and learning about science in general. The purpose of this study is to determine whether or not sixth graders' understanding of content from all six continents is enhanced by the use of puzzle media. This study used a qualitative methodology based on descriptive techniques. In order to fit in with the current sixth grade curriculum at SD Negeri 1 Kanan in Sindang District, Indramayu Regency, this study was conducted on November 21, 2024, for the 2023–2024 school year. The 28 participants in this study were sixth graders from SDN 1 Jurun; 13 of them were male and 15 were female. The purpose of this study is to examine whether or not sixth graders may benefit from using puzzle media to enhance their learning. Methods for gathering information include watching them, having them fill out surveys, and keeping detailed records. Using puzzle media for learning has been a huge success so far. Learning becomes more engaging and interactive with the use of this medium, which also helps develop abilities like agility and patience. In order to encourage their pupils, teachers should strive to create a dynamic learning environment.